Perceived Effect of Pastoralism on Arable Crop Production in Ido Local Government Area of Oyo State, Nigeria - Aderinto, Aderanti; Isiaq, Temitope S.; Ewebiyi, I. O.; Aderounmu, A. F. (NIU Journal of Humanities; Vol 4 No 4 (2019): KIU Journal of Humanities, Vol. 4 No. 4, December 2019, 2020)
In recent time, intense pastoralism has been impacting on arable farming across Nigeria. The study assessed arable crop farmers' perception of effect of pastoralism on arable crop production in Ido Local Government Area of Oyo State, Nigeria. Multistage sampling technique was used to select 125 arable crop farmers from 9 villages in 2 functional Agricultural Development Programme (ADP) extension cells noted for pastoralism. Interview schedule was used to collect data on respondents' socio-economic characteristics, pastoralism challenges, consequences of identified challenges, adaptation against pastoralism challenges and opinion on reducing pastoralism challenges. Data were analysed using descriptive and inferential statistics at p=0.05. Majority were â‰¤50 years old (60.0%), males (90.4%) and had education below secondary school (81.6%). Respondents' average farm size, farming experience and annual income were 2.1 hectare, 26.5 years and N236368.00 / $775.00 respectively. Identified pastoralism challenges include crop destruction (99.2%), water pollution (96.0%) and harassment from pastoralists (94%). Consequences of pastoralism include low income (90.4%) and reduced farming hours due to fear of attack (74.4%). Adopted mitigation measures include dialogue (87.2%) and extension intervention (84.8%). Farmers expressed strong view that culpable pastoralists should pay compensations for crop damage (98.4%) and development of hay and silage markets (97.6%). Significant relationship existed between age (Ï‡ 2 =8.550, p< 0.05) and sex (Ï‡ 2 =0.107, p<0.05) of the respondents and their perception of effects of pastoralism on arable crop production. Pastoralism is exerting negative effects on arable crop farming activities in the study area. Farmers and pastoralists should therefore pursue dialogue moderated by government for improved relationship. Keywords: Pastoralism, Arable Crops, Effect, Mitigation